Municipal socialism - Holland, John Warren (My University, 1896)
Introduction: The rapid increase of unborn population over rural means to the thoughtful man that in a comparatively few years the great masses of the people will live in cities. Small cities will grow larger, new cities will spring up and the percent of rural dwellers will gradually decrease until it will no longer demand consideration. This fact has turned the tide of thought in a new direction. Government is becoming more intensive. The question now before the public is not so much, How shall we govern our state or nation? But, How shall we govern our cities? We now find ourselves confronted with the problem of municipal government. In what manner shall we conduct the government of our cities so the greatest number may receive the greatest good? And what form of city government shall we have? It is proposed by some that city governments shall be miniature kingdoms; each city to be ruled over by one called whoever may be, but possessing power not unlike that of a king. Others propose a purely democratic government but fail to define the limits of such government; other theories are not wanting and among these is to be found that known as municipal socialism.
Citation: Holland, John Warren. Municipal socialism. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Municipal socialism; Government municipalities; Political science; Theses; Manuscripts (documents)